On-Surface Synthesis of a Large-Scale 2D MOF with Competing π-d Ferromagnetic/Antiferromagnetic Order - Frezza, Federico; Kumar, Manish; Sánchez-Grande, Ana; Soler-Polo, Diego; Carrera, Manuel; Stetsovych, Oleksandr; Mutombo, Pingo; Curiel, David; Jelínek, Pavel (Journal of the American Chemical Society, 2025)
Metal-organic frameworks (MOFs) represent an interesting class of versatile materials with important properties, including magnetism. However, the synthesis of atomically precise large-scale 2D MOFs with nontrivial strong magnetic coupling represents a current research challenge. In this regard, we report on the synthesis of a high-quality large-scale 2D MOF, with strong π-d magnetic exchange coupling. To this aim, we present a new two-step synthetic approach that consists of the initial formation of an extended supramolecular organic framework on a Au(111) surface, establishing the large-scale order of organic ligands and their subsequent metalation by single cobalt atoms assisted by annealing. Moreover, we show that the usage of radical asymmetric organic ligands enables us to form a magnetic 2D MOF with strong π-d electron interactions. According to the multireference calculations, the 2D MOF shows complex spin interactions beyond the traditional superexchange mechanism, with the interplay between antiferromagnetic and ferromagnetic couplings. We anticipate that this synthetic strategy can be adapted to different approaches, such as liquid interfaces or insulating substrates, to synthesize high-quality 2D MOFs. Accompanied by the high control with atomic precision over the magnetic properties of the ligands and metals, this approach enables the formation of large-scale 2D MOFs with complex spin interactions, which will open new avenues in the field of 2D magnetic materials.